Mucoadhesive Buccal Films for Local Delivery of Lactobacillus brevis - Angela Abruzzo; Beatrice Vitali; Francesca Lombardi; Luca Guerrini; Benedetta Cinque; Carola Parolin; Federica Bigucci; Teresa Cerchiara; Catia Arbizzani; Maria Caterina Gallucci; Barbara Luppi (MDPI AG, 2020)
The aim of this work was to prepare mucoadhesive buccal films for local release of Lactobacillus brevis CD2, which shows interesting anti-inflammatory properties due to its high levels of arginine deiminase. Hydroxypropylmethylcellulose-based films were prepared by means of a modified casting method, which allowed L. brevis CD2 loading on one side of the film, before its complete drying. Three batches of films were prepared, stored at +2−8 °C and +23−25 °C for 48 weeks and characterized in terms of physico-chemical and functional properties. For each batch, the L. brevis viable count and arginine deiminase activity were evaluated at different time points in order to assess functional property maintenance over time. Moreover, the mucoadhesive properties and ability of the films to release L. brevis CD2 were evaluated. A good survival of L. brevis CD2 was observed, particularly at the storage temperature of +2−8 °C, while the activity of arginine deiminase was maintained at both temperature values. Films showed good mucoadhesive properties and guaranteed a prolonged release of viable lactobacilli, which can be directed towards the whole buccal cavity or specific mucosa lesions. In conclusion, the proposed preparative method can be successfully employed for the production of buccal films able to release viable L. brevis CD2 cells that maintain the anti-inflammatory enzymatic activity.